If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + d = 3 Solving -4 + d = 3 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + d = 3 + 4 Combine like terms: -4 + 4 = 0 0 + d = 3 + 4 d = 3 + 4 Combine like terms: 3 + 4 = 7 d = 7 Simplifying d = 7
| 0=q-14 | | lgx=-5 | | 8z+15=3z-20 | | y/6=-1 | | 7w+4=2(7w-5) | | (7x^2+17x+13)-(12x^2+10x+4)=0 | | 3y-4x=6Fory | | -3(r+7)=-55 | | 7y+2x=5 | | x=5y+8.75 | | 3(m+31)=33 | | (x+1)-(x^2+2)=0 | | 14=-7/9v | | 7t-11=24 | | 3x^2-2y^3+6x=0 | | -5(1+6x)+3x=21-x | | 4x-9=6x-21 | | X+y+(x+41)=887 | | -2/3n=32/9 | | y=1000(1.75)t | | 4x-9+4y+8=180 | | -250x+100=600 | | 2-6z=8 | | 2x/3x=5 | | X-5/y-4 | | 16x-10x+9=99x-30 | | 10ab/4b | | 2a-4/a-2 | | 6x+10y=88 | | 7+4b=-7(-4b-1) | | 2n-4=236 | | 1.03-4=-2.15p+8.72 |